Utilizing Technological Pedagogic Content Knowledge (TPACK) To Improve Digital Economic Literacy - Syahrul Munir; Khofifatu Rohmah Adi; Sandi Purwanto (International Journal of Economics and Management Sciences, 2024)
Education is a basic component that can determine whether a country is progressing or not, which is also closely related to literacy. Where the activities and processes in it are a more detailed part of literacy, one of which is Economic Digital Literacy. The aim of this research is to determine the role of Technological Pedagogical Content Knowledge (TPACK) in increasing Digital Economic Literacy which is categorized as still low. The method used is a literature review whose sources are obtained from the Google Scholar website as well as reputable international journals with publications less than 10 years old. The results of the analysis of various literature reviews show that Technological Pedagogical Content Knowledge (TPACK) participates in increasing Economic Digital Literacy. The implementation of TPACK will have a positive impact on the flow of learning with a combination of knowledge, pedagogy, technology. With the combination of knowledge, pedagogy, technology, TPACK's role is able to increase Digital Economic Literacy.